Characterization of Hop Extracts and Extracts from some Selected Nigerian Plants by GC-MS and Brewing Qualities Analyses - Okafor, Vincent Nwalieji; Anyalebechi, Regina Igwe; Okafor, Ugochukwu Wilson (IJRDO-Journal of Applied Science, 2016)
Humuluslupulus L (hop) plants and four selected Nigerian plants namelyAzadirachtaindica(neem), Garcinia kola (bitter cola), Gongronemalatifolium(heckel) andVernoniaamygdalina (bitter leaf) as substitutes for hops in beer brewing werecharacterized in terms ofmethanolic and aqueousextracts using Gas Chromatography -Mass Spectrometer (GC-MS-Q2010 plus, Shimadzu, Japan). The brewing qualities (isoalphaacid and essential oil contents)of the extracts were investigated using standardmethods. Statistical analysis was carried out on the result of brewing qualities tests by theapplication of one way analysis of variance (ANOVA). The GCMS results showed thatthese plants contained metabolites comparable to those of hops, although somemetabolites[dehydro-cohumulunic acid; 4,4-dimethyl-2-buten-4-olide; 1,2-dimethylcyclopropanecarboxylic acid; lupulone; 2,5-dimethyl-2-hexanol; 4,4,5,5-tetramethylbicyclohexyl-6-ene-2,3-dione; octadecanoic acid, oxiranyl methyl ester and 1,2-benzenedicarboxylic, bis(-2-ethyl hexyl) ester] present in hops were absent in the Nigerianplants. Isomerized hop, hop leaf, G. kola and V. amygdalinacontained a total number of 14,11, 12 and 9 metabolites respectively while A. indcaand G. latifolium each contained atotal number of 10 metabolites.The brewing qualities investigated showed that iso-alphaacid ranged from 8.78-12.53ppm and essential oil ranged between 5.44-10.12g/100g. Thisstudy revealed that the brewing qualities of all the extracts did not differ significantly.Hence, extracts from tested Nigerian plants present potential substitutes for hops in theNigerian brewing industry without significant alteration to the brewing qualities.Consequently, academic activity in the area of mixtures/blends of extract of plant specieswhich mimic hop taste is strongly recommended.